STRUCTURAL AND FUNCTIONAL ASPECTS OF ENGLISH WORD ORDER - Buriev Dilmurod Arzimurodovich; Pardayev Ruslan Tavakkal ugli (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT This article paper is to study Structural and functional aspects of English word order, its types, degrees of comparison and its functions in the sentence. The article is to study word order as a part of speech, its grammatical categories and its formation in the English and Uzbek languages.